This page does not represent the most current semester of this course; it is present merely as an archive.

Proof techniques we’ve learned so far:

See also §3.3 and §3.4.2, as well as our list of equivalences.

In a small step proof, write an equivalent expression and cite the rule used to reach it. If several rules are needed, write them out one by one.

The following uses a note per line to show how it is equivalent to the preceding line

1 | A \lor (B \lor C) | |

2 | (A \lor B) \lor C | Associative property of \lor |

3 | (B \lor A) \lor C | Commutative property of \lor |

4 | B \lor (A \lor C) | Associative property of \lor |

5 | (\lnot (\lnot B)) \lor (A \lor C) | Double negation |

6 | (\lnot B) \rightarrow (A \lor C) | Disjunction ot implication |

In a prose proof, write the original and the new expression, separated by can be re-written as

or is equivalent to

. Only include intermediate steps or identified proof rules if you believe your audience would take more than a few minutes to figure them out themselves. Common shortcut phrases for guiding through steps include

- Rearranging
- Utilizing the associative, commutative, and distributive properties of operators
- Simplifying
- Removing double negation and the ones and zeros effects of tautologies and contradictions

This is the same example as the previous one, but written in prose style instead.

A \lor (B \lor C) can be re-written as (\lnot \lnot B) \lor (A \lor C), which is equivalent to (\lnot B) \rightarrow A \lor C by the equivalence of implication and disjuction.

See also §1.7, ∀x 17.5, and our proof of one of De Morgan’s laws

State a disjunctive tautology. For a simple tautology like P \lor \lnot P, stating it is enough; for more complicated tautologies, you may need to add a sub-proof or lemma

^{1}that it*is*tautological.Then proceed to consider several cases: one for each term of the disjunctive tautology, in each case assuming that that clause is true.

After completing all of the cases, the full proof is also completed:we may not know

*which*case’s assumption is true, but because the disjunction is a tautology, we know at least one of them*must*be.

This is a full proof of one of our known equivalences

P \rightarrow Q \equiv \lnot P \lor Q

Either P is true or P is false.

- Case 1: P is true
The expression P \rightarrow Q in this case is equivalent to \top \rightarrow Q, which can be simplified to Q.

The expression \lnot P \lor Q in this case is equivalent to \bot \lor Q, which can be simplified to Q.

Since the two are equivalent to the same thing, they are equivalent to each other.

- Case 2: P is false
The expression P \rightarrow Q in this case is equivalent to \bot \rightarrow Q, which can be simplified to \top.

The expression \lnot P \lor Q in this case is equivalent to \top \lor Q, which can be simplified to \top.

Since the two are equivalent to the same thing, they are equivalent to each other.

Since P \rightarrow Q \equiv \lnot P \lor Q is true in both cases, it is true in general.

Case analysis in small-step proofs involves embedded sub-proofs, as is described in ∀x 17.5 and used in ∀x 17.1 and ∀x 19.6.

See also our list of entailments.

Applying entailment is very much like applying equivalence rule, except it only needs to work in one direction. Because A \equiv B implies A \vDash B, you can use equivalence rules in a proof that applies entailment.

There are many more entailments (sometimes called proof rules

or inference rules

) than there are equivalence rules, so using them can make proof construction much easier than limiting yourself to equivalences.

A proof that only uses proof rules is sometimes called a *direct proof*.

- Assume the negation of what you want to prove.
- Use other proof techniques to derive \bot.
- State
because assuming \lnot A led to a contradiction, A must be true

or the equivalent in other words.

There is no largest real number.

Assume there is a largest real number. Call that largest real number x; because it is the largest, we know that \tag{1} \forall y \in \mathbb R \;.\; y \le x

Consider the number x+1. Because x and 1 are both real numbers and the reals are closed over addition, x+1 \in \mathbb R. Thus, we can instantiate (1) with y = x+1 to get x+1 \le x. But clearly x+1 > x, which is a contradiction.

Because assuming there is a largest real number led to a contradiction, there must be no largest real number.

Proof by induction, in its purest form, only works for theorems of the form \boxed{\forall n \in \mathbb N \;.\; P(n)} where P is a predicate. However, many other proofs can be reduced to that form.

- State you are using induction.
- Identify one or more base cases, which are P(0) and (if needed) P(1), P(2), etc.; prove each using other proof techniques.
- Add an inductive step of the form
assume P(n)

and then prove P(n+1); if needed, you can assume \boxed{\forall i \in \big\{ i \;\big|\; i \in \mathbb N \land i \le n \} \;.\; P(i)} instead (calledstrong induction

) if needed. - State that by the principle of induction, the theorem holds for all n \in \mathbb N.

\mathbb N \subseteq \mathbb R

Note that by the definition of subsets, this is equivalent to proving \boxed{\forall n \in \mathbb N \;.\; n \in \mathbb R}, so we’ll use P(n) = n \in \mathbb R as our predicate.

We proceed by induction.

- Base case
- 0 \in \mathbb R by definition.
- Inductive case
- Assume n \in \mathbb N and n \in \mathbb R. Consider x = n+1; because 1 \in \mathbb R and the reals are closed under addition, x \in \mathbb R.

By the principle of induction, it follows that \forall n \in \mathbb N \;.\; n \in \mathbb R. By the definition of subsets, that means \mathbb N \subseteq \mathbb R.

Induction is used so often that the template is often applied with fairly dramatic modifications, possibly even having multiple inductive steps, without explicitly noting those modifications.

If a string is created by starting with

and optionally replacing an `a`

with `a`

or a `ab`

with `b`

, as many times as you want, the result will always have an odd number of `aa`

s.`a`

It is also true that any string consisting of an odd number of `a`

s, each followed by any number of `b`

s, can be created with this process, but let’s start with this easier odd-number proof first.

We proceed by induction.

- Base case

has one`a`

, which is an odd number.`a`

- Inductive case
Assume a string s has an odd number of

s. Consider the a string t created in one step from s.`a`

- Case
`a`

to`ab`

- Suppose t was created by replacing one

in s with`a`

. t has the same number of`ab`

s as s, so by our assumption t has an odd number of`a`

s.`a`

- Case
`b`

to`aa`

- Suppose t was created by replacing one

in s with`b`

. t has exactly two more`aa`

s than s, and 2 + an odd number is still odd, so by our assumption t has an odd number of`a`

s.`a`

Since t has an odd number of

s in each case, it has an odd numebr of`a`

s in general.`a`

- Case

By the principle of induction, it follows that all strings created using this process have an odd number of

s.`a`

Implicitly, the above proof used induction on the number of steps used to create the string, but that was never identified in the proof itself.

a lemma is a helper proof made before the main proof it will be used inside of↩︎